2019
DOI: 10.1007/s13197-019-03774-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process parameters on hydroxymethylfurfural content, diastase and invertase activity of coriander honey

Abstract: Floral authenticity of coriander (Coriandrum sativum) honey samples was confirmed by melissopalynology. Effect of temperature, time and pH on quality parameters i.e. hydroxymethylfurfural (HMF) content, diastase and invertase activity of coriander honey was analysed using response surface methodology. Central composite rotatable design was adopted for optimization of process variables. An increased in HMF content was observed with increase in temperature and pH whereas diastase activity decreased with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Briefly, the high diastase and invertase activities imply that honey is raw honey that does not heat (Sahin et al 2020). Unlike invertase and diastase activities, low glucose oxidase activity indicates high-quality raw honey (Bankar et al 2009, Kamboj et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the high diastase and invertase activities imply that honey is raw honey that does not heat (Sahin et al 2020). Unlike invertase and diastase activities, low glucose oxidase activity indicates high-quality raw honey (Bankar et al 2009, Kamboj et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Karabournioti and Zervalaki (2001) found that the increased levels of HMF in honeys of several botanical origins kept at various temperatures for 24 h were correlated with the temperatures Shapla et al (2018) reviewed HMF concentrations of honey samples from 29 countries after storage for up to three years at temperatures up to 30°C; there was a clear trend for increasing HMF levels with longer storage times and higher storage temperatures, the highest value being 1,132 mg/kg in a Malaysian honey kept at 30°C for more than 2 years. The importance of time and temperature for the level of HMF was confirmed in a controlled study with coriander honey (Kamboj et al, 2019), but the authors emphasize that other factors such as pH, water content, sugar profile, presence of organic acids and floral source of the honey may also have an effect. The multifactorial reasons for HMF formation may explain the highly variable HMF levels reported in the review by Shapla et al (2018).…”
Section: Concentration Of Hmf In Honey and Various Bee Feedsmentioning
confidence: 98%
“…Eventually, the secondary, tertiary, and quaternary protein structures unfold, leading to denaturation (Lee et al., 2022). On the other hand, it is important to note that the optimum pH for enzymatic activities of the invertase enzyme is pH 6, and for the diastase enzyme, it is pH 4.6 (Kamboj et al., 2019; Shankar et al., 2014). However, most of the studies presented an increasing trend of free acidity during the storage period (Table 1).…”
Section: Physicochemical Propertiesmentioning
confidence: 99%